Modern art as the end of art. Romanticism as an overcoming of symbolism and classicism - Vieweg, Klaus (Estudios de Filosofía, 2005)
In the paper the author faces the famous and very diversely interpreted hegelian thesis of the end of art as the supreme way to perceive truth or the spirit. In this confrontation, the author tries to penetrate the significance that modernity has (and this doesn’t mean only modern art), in the context of hegelian philosophy of art In the explanation of such a significance, the author concedes a decisive value to the hegelian concept of “subjectivity”, as a founding concept of modernity and also as an identifier of it. He poses in this conception the speculative horizon from which the idea of the end of an, far from being a sentence of death of art, auto-presents itself as the immanent moment in the realization of the free and spiritualized subjectivity. The end of art would be, therefore, the beginning of the history of human freedom, the beginning of human existence as such.